REORIENTASI REFORMASI BIROKRASI DAN GOOD GOVERNANCE DALAM PENYELENGGARAAN SEKTOR PUBLIK DI INDONESIA - Ii Sumantri (GoAcademica Research dan Publishing, 2022)
In order for a country to run well, it is necessary to have a well-run public bureaucracy. But unfortunately, the perception of the bureaucracy in Indonesia itself is very bad, where the bureaucracy is considered as convoluted, too many rules and very inefficient. This research then aims to look at how bureaucratic reform and good governance are reoriented in organizing the public sector in Indonesia. This research will be carried out using a descriptive qualitative approach. The data used in this study were obtained from various research results and previous studies. The results of this study then found that a clean and democratic government system must be a priority for society and government. Efforts to achieve this can be carried out through the application of the principles of good governance. In its implementation, governance reorientation can be carried out by involving stakeholders, the public and the private sector.